n2 + 3 \(\div\) n - 1
=> ( n2 - 1 ) + 4 \(\div\) n - 1
=> ( n - 1 )( n + 1 ) + 4 \(\div\) n - 1
Vì: ( n - 1 )( n + 1 ) \(\div\) n - 1
=> 4 \(\div\) n - 1
=> n - 1 \(\in\) Ư(4) = { - 4; - 1; 1; 4 }
=> n \(\in\) { - 3; 0; 2; 5 }
Vì: n \(\in\) N nên n \(\in\) { 0; 2; 5 }
Vậy: n \(\in\) { 0; 2; 5 }
n2 + 3 chia hết cho n - 1
=> (n2 - 1) + 4 chia hết cho n - 1
=> (n - 1)(n + 1) + 4 chia hết cho n - 1
Vì (n - 1)(n + 1) chia hết cho n - 1
=> 4 chia hết cho n - 1
=> n - 1 \(\in\) Ư(4) = { + 1; + 2; + 4 }
=> n \(\in\) {-3; 0; 2; 5; -1; 3}
Vậy ...
574+366+6332+789
=532+768+856
=456+7854
=54436
Giải :
Vì n2 + 3 ⋮ n - 1 nên ( n2 - 1 ) + 4 ⋮ n - 1
⇒ ( n - 1 ) ( n + 1 ) + 4 ⋮ n - 1
Vì n - 1 ⋮ n - 1 . Để ( n - 1 ) ( n + 1 ) + 4 ⋮ n - 1 <=> 4 ⋮ n - 1 ⇒ n - 1 ∈ Ư ( 4 ) = { + 1 ; + 4 }
Ta có : n - 1 = 1 ⇒ n = 2 ( nhận )
n - 1 = - 1 ⇒ n = 0 ( nhận )
n - 1 = 4 ⇒ n = 5 ( nhận )
n - 1 = - 4 ⇒ n = - 3 ( nhận )
⇒ n ∈ { - 3 ; 0 ; 2 ; 5 }
Happy new year 2016